Odpowiedzi

Najlepsza Odpowiedź!
2009-11-03T19:55:17+01:00
Rozwiąż równanie
a) (5x-2)(x+7)(4-1/3x)=0
5x-2=0 v x+7=0 v 4-1/3x=0
x=2/5 v x=-7 v 4=1/3x
x=2/5 v x=-7 v x=12
b) 5=3x+5x⁴-3x⁵
3x+5x⁴-3x⁵-5=0
-x⁴(3x-5)+3x-5=0
(3x-5)(-x⁴+1)=0
3x-5=0 v -x⁴+1=0
x=5/3 v x⁴=1
x=5/3 v x=-1 v x=1
c) x⁵-6x⁴=40x³
x⁵-6x⁴-40x³=0
x³(x²-6x-40)=0
x=0 Δ=36+160=196
x=0v x₁=(6-14):2=-4 v x₂=(6+14):2=10
d) x⁶-x⁴-2x²=0
x²(x³-x²-2)=0
x²=0 v x³-x²-2=0
x=0
2009-11-03T20:16:59+01:00
A) (5x-2)(x+7)(4-1/3x)=0
5x-2=0 v x+7=0 v 4-⅓x=0
x=²/₅ v x=-7 v x=12, bo -⅓x=-4 >> x=(-4)*(-3)

b) 5=3x+5x⁴-3x⁵
3x-5+5x⁴-3x⁵=0
-1(5-3x)+x⁴(5-3x)=0
(x⁴-1)(5-3x)=0
(x²-1)(x²+1)(5-3x)=0
(x-1)(x+1)(x²+1)(5-3x)=0
x=1 v x=-1 v x=⁵/₃, bo -3x=-5
x²+1 jest nierozkładalne i nie ma pierwiastków

c) x⁵-6x⁴=40x³
x³(x²-6x)=40x³ / :x³
x²-6x=40
x²-6x-40=0
Δ=36+4*40=36+160=196
√Δ=14
x₁=(6-14)/2=-8/2=-4
x₂=(6+14)/2=20/2=10

d) x⁶-x⁴-2x²=0
x²(x⁴-x²-2)=0 /: x²
x⁴-x²-2=0
podstawiam x²=t
t²-t-2=0
Δ=1+4*2=9
√Δ=3
t₁=(1-3)/2=-2/2=-1
t₂=(1+3)/2=4/2=2
Wracam do podstawienia
x²=t
x²=-1 >>Sprzeczność
x²=2 >> x=√2